The healthcare needs and general practice utilization of people with acquired neurological disability and complex needs: A scoping review - Stacey Oliver; Jacinta Douglas; Dianne Winkler; Christopher Pearce; Ella‐Rose Minter; Hannah K. Jarman; Megan Topping (Wiley, 2022)
Abstract Background For people with acquired neurological disabilities and complex needs, general practitioners (GPs) play an important role in health management and early intervention for the prevention of comorbidities and health complications. People with disability are a vulnerable group who need and have the right to, quality general practice services. It is therefore important to understand the health needs and service use of this group. The aim of this review was to identify the healthcare needs and general practice utilization of people with acquired neurological disabilities and complex needs. Methods A scoping review methodological framework was utilized. Six databases (MEDLINE, PsycInfo, CINAHL, Scopus, Embase and the Cochrane Library) were searched. Articles were included if they reported on general practice service utilization of people with acquired neurological disabilities and complex needs aged between 18 and 65. Articles were required to be peer‐reviewed, written in English and published between 2010 and 2021. Results Thirty‐one articles were included in the review. Studies originated from Canada (9), the United States (8), Australia (4), Switzerland (4), the United Kingdom (2), England (1), Norway (1), France (1) and Denmark (1). For many people, GPs were the main healthcare provider. People with disability consult multiple healthcare providers and navigate complex healthcare systems. Commonly presented healthcare needs were bladder, bowel and skin problems, pain and chronic pain, medication needs and mental health concerns. Conclusions People with acquired neurological disabilities and complex needs were vulnerable to receiving suboptimal healthcare. The literature highlighted issues regarding the accessibility of services, the fragmentation of health services and inadequate preventative care. GPs were challenged to offer adequate disability‐related expertise and to meet the mental health needs of people with disability within time constraints. Patient and Public Involvement This manuscript was prepared in collaboration with a GP, who is one of the authors. A person with lived experience of acquired neurological disability was engaged to check the alignment of the findings with their personal experience and provide feedback.